Assessment of antioxidant, antimicrobial and wound healing potential of golden chicken fern (Cibotiumbarometz (L.)J. Sm.) methanolic extracts - Rosdin, Nursyamila Izzatie; Khayat, Mohd Ezuan; Chia, Suet Lin; Halim, Murni; Wasoh, Helmi; Sobri, Zulfazli M. (Hibiscus Publisher Enterprise, 2024)
Cibotium barometz (L.)J. Sm., also known as the golden chicken fern, is valued in traditional Chinese medicine, particularly for its rhizome and golden hairs, which are reputed to have medicinal properties. However, there is limited scientific evidence supporting the wound-healing properties of its golden hairs. This study aims to evaluate the antioxidant, antimicrobial, and wound-healing potential of extracts from these hairs. The golden hairs were extracted with 80% methanol to isolate bioactive compounds. Antioxidant activity was measured using the DPPH radical scavenging assay, and total phenolic content (TPC) and total flavonoid content (TFC) were assessed. TFC was found to be higher than TPC, with values of 331 ± 0.011 mg QE/g and 67.36 ± 0.014 mg GAE/g, respectively. The antimicrobial properties of the extract were tested against Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Serratia marcescens using agar well diffusion; no inhibition zones were observed, indicating a lack of antimicrobial activity. Further assays, including cytotoxicity and wound scratch tests on normal human dermal fibroblast (NHDF) cells, revealed that the extract did not promote wound healing and suppressed NHDF cell growth at a concentration of 10 mg/mL. In conclusion, while C. barometz golden hairs are traditionally valued, this study found limited antioxidant activity and no antimicrobial or wound-healing efficacy in the extract.